PELATIHAN PENGGUNAAN EJAAN UNTUK MENINGKATKAN KEMAMPUAN MENULIS IKLAN BAGI IBU RUMAH TANGGA DUSUN CIWAHANGAN DESA KECAMATAN BAREGBEG KABUPATEN CIAMIS - Agustini, Rina; Andini, Siti (Galuh International Journal of Community Service and Development, 2024)
Most housewives in Ciwahangan Hamlet do not have additional income. Housewives can help market blacksmith products through advertising so that they can help husbands increase income for their families. To improve the skills of housewives, community service activities were carried out which aimed to increase the knowledge of spelling and the ability to write advertisements for housewives in Ciwahangan Hamlet, Baregbeg Village, Baregbeg District, Ciamis Regency. This service activity is carried out through planning stages including observation activities to determine the condition of housewives' abilities in using spelling and writing advertisements. Coordination is carried out by meeting the village government and community leaders to ask for permission to carry out activities. Socialization is carried out to convey the technical implementation of activities and things that mothers must prepare while participating in activities. The implementation stage includes providing material on spelling and writing advertisements. The mentoring stage is through mentoring activities in uploading advertisements on Facebook social media. Based on the results of the evaluation that has been carried out, an increase in the ability to use spelling in advertisements is obtained, namely the use of letters by 80%, writing words by 70%, and the use of punctuation by 85%. Apart from that, participants are also able to create advertisements on Facebook social media